Experimental investigation of nano materials applicability in Hot Mix Asphalt (HMA) - Zahid, Awais; Ahmed, Sarfraz; Irfan, Muhammad (Construction & building materials, 2022)
•The efficacy of using Nano materials in Hot Mix Asphalt (HMA) was examined.•The effect of CNT and NC, loading frequency and temperature on dynamic modulus and resilient modulus were investigated.•Nano materials (CNT and NC) led to higher stiffness improved Dynamic stability rutting resistance and moisture resistance of HMA.•The optimized percentage of CNT and 1.5% CNT with NC in HMA was determined to be 1.5% and 6%, respectively.•MEP and regression techniques was developed in predicting the dynamic modulus of the nano material modified HMA. Nanotechnology for asphalt modification and incorporating nanomaterials into Hot Mix Asphalt (HMA) to deal with road failure have gained popularity recently. Researchers have reported the improved performance of asphalt modiﬁed by nanomaterials but most of the study is limited to binder modification using nanomaterials. The utilization of Nanomaterials in HMA can significantly improve the performance indicators in the form of extension in pavement service life and decrease pavement distresses. The Nanomaterials reinforcement of HMA can enhance pavement performance indicators, including low and high-temperature dynamic modulus and stability and enhancement in rut resistance and stiffness modulus. Nano Materials modified is a suitable solution to improve the mechanical properties of HMA. The current study objectives focus on the experimental investigation of Nano Materials such as Carbon Nano Tubes (CNT) and Nano Clay (NC) applicability in HMA. CNT and NC percentages used in HMA to the weight of bitumen are 0.5%, 1.5%, 2.5% and 2%, 4%, 6%, 8%. Conventional and Nanomaterial modified asphalt mixes were subjected to performance tests such as Simple Performance Tester (SPT), Dynamic Stability and Rutting, Tensile Strength Ratio (TSR), and Resilient Modulus (MR) using UTM-25. The present study further aimed to predicting dynamic modulus of nanomaterial modified HMA through Artificial intelligence (AI) modeling using Multi Expression Programming (MEPX) and Regression modelling with validation. Results have indicated that the addition of CNT and NC has improved HMA properties such as enhancement in dynamic modulus and dynamic stability and improves stiffness, rut resistance, and moisture resistance. It has been observed that 1.5% CNT with 6% NC content by weight of bitumen in asphalt mixtures outperformed other CNT and NC percentages. Moreover, Dynamic stability and Rut resistance have been improved by 820% and 64.7%, respectively, while resilient modulus increased by 309% and moisture susceptibility has been reduced by 22.26%. Overall, the asphalt mixtures with 1.5% CNT with 6% NC content has the best results.